New approach methodologies based prediction for pulmonary toxicity - Jooyeon Lee; Dahee Han; Se-Ran Yang (Toxicological Research, 2026)

Mediation Effect of Oxidative Stress in the Associations between Cadmium Exposure and Renal Tubular Damage of Residents in Metal-Polluted Regions in Korea - Dahee Han; Kyung-Hwa Choi; Jang-Hee Lee; Young-Seoub Hong; Woo Jin Kim; Yong Min Cho (Exposure and Health, 2026)

The role of Alu elements in causing BRCA1 structural variation and breast cancer susceptibility - Minjae Yu; Dahee Jo; Wonseok Shin; Kyudong Han (Genes & Genomics, 2026)

Analysis of current technology status for the industrialization of cultured meat - Da Young Lee; Jinmo Park; Dahee Han; Yeongwoo Choi; Jin Soo Kim; Ermie Mariano; Juhyun Lee; Seung Hyeon Yun; Seung Yun Lee; Sungkwon Park; Suk Ho Bhang; Sun Jin Hur (Critical Reviews in Food Science and Nutrition, 2025)

A review on the characterization of edible scaffolds for cultured meat: Physical, chemical, biocompatibility, and food safety evaluation methods - Ermie Mariano; Da Young Lee; Juhyun Lee; Yeongwoo Choi; Jinmo Park; Dahee Han; Jin Soo Kim; Ji Won Park; Seok Namkung; Sun Jin Hur (Food Chemistry, 2025)

Crusting-fabricated three-dimensional soy-based scaffolds for cultured meat production: A preliminary study - Ermie Mariano; Da Young Lee; Seung Hyeon Yun; Juhyun Lee; Yeong Woo Choi; Jinmo Park; Dahee Han; Jin Soo Kim; Inho Choi; Sun Jin Hur (Food Chemistry, 2024)

Environmental risk score of multiple pollutants for kidney damage among residents in vulnerable areas by occupational chemical exposure in Korea - Hyuna Jang; Kyung-Hwa Choi; Yong Min Cho; Dahee Han; Young Seoub Hong (Environmental Science and Pollution Research, 2024)
This study aimed to develop an environmental risk score (ERS) of multiple pollutants (MP) causing kidney damage (KD) in Korean residents near abandoned metal mines or smelters and evaluate the association between ERS and KD by a history of occupational chemical exposure (OCE). Exposure to MP, consisting of nine metals, four polycyclic aromatic hydrocarbons, and four volatile organic compounds, was measured as urinary metabolites. The study participants were recruited from the Forensic Research via Omics Markers (FROM) study ( n = 256). Beta-2-microglobulin (β2-MG), N-acetyl-β-D-glucosaminidase (NAG), and estimated glomerular filtration rate (eGFR) were used as biomarkers of KD. Bayesian kernel machine regression (BKMR) was selected as the optimal ERS model with the best performance and stability of the predicted effect size among the elastic net, adaptive elastic net, weighted quantile sum regression, BKMR, Bayesian additive regression tree, and super learner model. Variable importance was estimated to evaluate the effects of metabolites on KD. When stratified with the history of OCE after adjusting for several confounding factors, the risks for KD were higher in the OCE group than those in the non-OCE group; the odds ratio (OR; 95% CI) for ERS in non-OCE and OCE groups were 2.97 (2.19, 4.02) and 6.43 (2.85, 14.5) for β2-MG, 1.37 (1.01, 1.86) and 4.16 (1.85, 9.39) for NAG, and 4.57 (3.37, 6.19) and 6.44 (2.85, 14.5) for eGFR, respectively. We found that the ERS stratified history of OCE was the most suitable for evaluating the association between MP and KD, and the risks were higher in the OCE group than those in the non-OCE group.

Enhanced safety of lithium ion batteries through a novel functional separator with encapsulated flame retardant and hydroxide ceramics - Youngjoon Roh; Dongyoung Kim; Dahee Jin; Dohwan Kim; Cheolhee Han; Jaecheol Choi; Hochun Lee; Young-Gi Lee; Yong Min Lee (Chemical Engineering Journal, 2023)